Dogs distinguish authentic human emotions without being empathic - Juliane Bräuer; Dorothea Eichentopf; Nomi Gebele; Louise Jandke; Veronique Mann; Katharina Schulte; Yana Bender (Animal Cognition)
Abstract Several recent studies have investigated how dogs perceive human emotional expressions. They have measured the reactions of dogs when exposed to stimuli presented in different modalities, such as photographs, audio recordings or odor samples, or to humans simulating various emotional situations. In the current study, dog owners were manipulated to genuinely experience emotions of happiness, sadness, and neutrality. We measured how dogs responded to their owners’ authentic emotions in two different natural situations: induction of the emotion through a video clip and training of a new task. Through a detailed analysis of dog behavior in these naturalistic settings, we investigated whether dogs show behavioral responses to genuine human emotions. We found that dogs behaved differently depending on the owner’s emotional state: they gazed and jumped less at owners when they were sad, and their compliance with the ‘sit’ command was also diminished. When owners were happy, dogs performed better in the trained task. These results are discussed in light of how dogs perceive human emotional expressions and the adaptive value of this skill.